Onco-mNGS facilitates rapid and precise identification of the etiology of fever of unknown origin: a single-centre prospective study in North China - Bingbing Liu; Tengfei Yu; Ruotong Ren; Na Wu; Nanshu Xing; Jingya Wang; Wenjie Wu; Xuefang Cao; Jingping Zhang (BMC Infectious Diseases)
Abstract Objectives Delayed diagnosis of patients with Fever of Unknown Origin has long been a daunting clinical challenge. Onco-mNGS, which can accurately diagnose infectious agents and identify suspected tumor signatures by analyzing host chromosome copy number changes, has been widely used to assist identifying complex etiologies. However, the application of Onco-mNGS to improve FUO etiological screening has never been studied before. Methods In this single-centre prospective study, we included 65 patients with classic FUO, who were randomly divided into control group (sample cultivation) and mNGS group (cultivation + Onco-mNGS). We analyzed the infectious agents and symbiotic microbiological, tumor and clinical data of both groups. Results Infection-related pathogenic detection efficiency rose from 25% (control group) to 48.48% (experimental group). Seven patients with chromosome copy number changes had later been confirmed tumors, indicating a 100% of clinical concordance rate of Onco-mNGS for tumors. In addition, the time frame for diagnosing or ruling out infection/tumor with Onco-mNGS had greatly reduced to approximately 2 days, which was 7.34 days earlier than that in the control group. Conclusions Onco-mNGS is an ideal rapid diagnostic aid to assist improving the early diagnostic efficiency of FUO-associated diseases.